Batam Green Initiative : Coastal Design Directives with Natural Innovations - Stivani Ayuning Suwarlan; Billy Shevriyanto; Angga Setiawan; Antoni Wijaya; Wahyu Leonardi (Universitas Internasional Batam, 2021)
The design and development of coastal areas is an effort to increase the value of a city. Utilizing the coastal potential of a city to become a center of destinations is one of the important things to promote and encourage the prosperity of the community in a city. Batam, is a province that is blessed with many and beautiful coastal areas, but not all coastal areas with such great potential have been touched and developed. In Batam by 2020, 30% of the regional revenue and expenditure budget (APBD) is used for infrastructure development. However, coastal areas that are still undeveloped will not be affected positively, therefore design directions are needed for coastal areas with great potential, such as the Batam Green Initiative site area, which has abundant mangrove forests. The research method used is qualitative research. Observations were made as a first step to determine the factual conditions of the research area using a walkthrough analysis. Then research was also carried out related to the condition of the community around the site area, related to their needs and whether the design directions made would maximize the site, and also have a positive impact on the surrounding community, especially from various aspects. The results showed that the potential for mangrove forests in the Batam Green Initiative and its hilly contours, make the Batam Green Initiative a potential site for coastal areas that can be maximized and promote the prosperity of the surrounding community.